ANALISIS SISTEM AKUTANSI DAN PENGENDALIAN INTERNAL DALAM PEMBELIAN BAHAN BAKU WIRE ROAD PADA PT. INTAN METALINDO - Nia Kurniati; Sarlina Sari; Ajat Sudrajat (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
PT Intan Metalindo is a company engaged in the industrial sector, mild steel construction. In order for production activities to continue running well, an accounting system is needed in purchasing raw materials as a very important part of the company, and of course internal control is needed in the management of a company to ensure the availability of these raw materials. This study aims to determine how the accounting system for the purchase of raw materials and how the internal control in the process of purchasing Wire Road raw materials at PT Intan Metalindo. This research was conducted with qualitative methods and data collection techniques were carried out by observation, interviews and literature study. The results of this study indicate that the accounting system for the purchase of raw materials and internal control in the company PT Intan Metalindo is quite good. namely the existence of a function section and transaction documents related to the purchase of Wire Road raw materials and in the internal control system at PT. Intan Metalindo has been running quite well, namely with the existence of an organizational structure in the separation of functions between sections, as well as the existence of an authorization system that is in accordance with the existing theoretical basis. However, in controlling the inventory of raw materials, there are still problems, namely the difference in the stock of raw materials. In this case, it is necessary to have a regular stock taking every 1 month, so that there is no difference in the stock of available raw materials.